Utilization of Mangosteen Extract to Enhance the Masculinization of Striped Snakehead (Channa striata) Fingerlings - Mardika, Hanisya Putri Kania; Pramono, Taufik Budhi; Afiyah, Novia Nurul; Putra, Joni Johanda; Larasati, Lorichika Gustinda; Rohmah, Siti Nur (Fakultas Perikanan dan Ilmu Kelautan Universitas 17 Agustus 1945 Cirebon, 2025)
Aquaculture technology to increase productivity includes sex reversal or masculinization. Masculinization of snakehead fish (Channa striata) is essential to balance the male sex ratio for sustainable aquaculture. One approach is the use of natural compounds to reduce dependence on synthetic hormones that are less environmentally friendly. Natural substances such as mangosteen peel extract (Garcinia mangostana) contain aromatase inhibitors. This study aimed to determine the optimal dosage of mangosteen peel extract for inducing sex reversal in snakehead fish. Two-week-old fry were immersed in different treatments (control 0 g/L, 0.5 g/L, 0.7 g/L, and 0.9 g/L) for 4 hours and reared for 2 months. Gonads were examined microscopically using aceto-carmine staining. Results showed that the highest male proportion was obtained at 0.9 g/L, while the highest survival rate was recorded at 0.7 g/L. The Kruskal–Wallis test (H=7.64; p=0.054) indicated no significant differences among treatments in male proportion. The Mann–Whitney U test (p=0.077) between control and each treatment confirmed that formal differences were not significant, although a trend of increased male proportion was observed across all treatments. One-way ANOVA (F=16.72; p=0.0008) demonstrated that treatment doses significantly affected survival. Tukey HSD revealed that all treatments differed significantly from control (p<0.05), while no significant differences occurred among treatment doses (p>0.05). In conclusion, doses of 0.5–0.9 g/L were effective in promoting masculinization while maintaining optimal survival in snakehead fish.